Ferroelastic–Ferroelectric Multiferroicity in van der Waals Rhenium Dichalcogenides. Issue 18 (28th March 2022) - Jeong, Jaehun; Kim, Hyeon‐Sik; Kwon, Gihyeon; Jeong, Kwangsik; Lee, Hyangsook; Lee, Ji Hye; Park, Myunguk; Lee, Changjun; Yu, Sanghyuck; Kim, Heegoo; Im, Seongil; Yoo, Kyunghwa; et al.
Abstract: 2D multiferroics with combined ferroic orders have gained attention owing to their novel functionality and underlying science. Intrinsic ferroelastic–ferroelectric multiferroicity in single‐crystalline van der Waals rhenium dichalcogenides, whose symmetries are broken by the Peierls distortion and layer‐stacking order, is demonstrated. Ferroelastic switching of the domain orientation and accompanying anisotropic properties is achieved with 1% uniaxial strain using the polymer encapsulation method. Based on the electron localization function and bond dissociation energy of the Re–Re bonds, the change in bond configuration during the evolution of the domain wall and the preferred switching between the two specific orientation states are explained. Furthermore, the ferroelastic switching of ferroelectric polarization is confirmed using the photovoltaic effect. The study provides insights into the reversible bond‐switching process and potential applications based on 2D multiferroicity. Abstract : Ferroelastic–ferroelectric multiferroic materials can switch orientations of crystal structure and polarization with external strain. 2D ferroelastic–ferroelectric multiferroicity in single‐crystalline rhenium dichalcogenides is discovered. Reorientation of the physical properties based on reversible bond switching between the rhenium atoms provides insights for 2D multiferroic phase transitions and opens up new opportunities for applications such as multilevel memory.